A multicenter retrospective study of patients with pulmonary hypertension transitioned from inhaled to oral treprostinil. (March 2021) - Zwicke, Diane L.; Restrepo-Jaramillo, Ricardo; Alnuaimat, Hassan; Gordon, Kathryn; Broderick, Meredith; Edwards, Lisa D.; Allmon, Andrew; Leary, Peter J.
Oral treprostinil has recently been shown to delay disease progression in patients with pulmonary arterial hypertension in a long-term outcomes study. The potential advantages of an oral formulation have resulted in patients transitioning from inhaled to oral treprostinil. The current study reports a retrospective analysis of patients who transitioned from treatment with inhaled to oral treprostinil. A multicenter retrospective chart review was conducted for 29 patients with pulmonary hypertension that transitioned from inhaled to oral treprostinil. Data were collected from inhaled treprostinil initiation and patients were followed until discontinuation of oral treprostinil or the end of the observation period. Persistence was calculated using Kaplan–Meier estimates. Prior to transition to oral treprostinil, patients had received inhaled treprostinil for a median of 643 (IQR: 322–991) days and 52% of patients were New York Heart Association/World Health Organization Functional Class III. For patients that cross-titrated between formulations, the median time to complete the cross titration was 24 (IQR: 1–57) days. At 16- and 24-weeks post-transition, oral treprostinil persistence was 86 and 76%, respectively. Persistence was 59% at 52 weeks post-transition. Clinical stability for the majority of patients at first follow-up post-transition was suggested based on available New York Heart Association/World Health Organization Functional Classification. Transitions from inhaled to oral treprostinil appeared safe and tolerable in the short-term. Additional prospective studies are needed to fully evaluate the safety and efficacy of transitions from inhaled to oral treprostinil.